If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 3(400 + -1n) = 1050 2n + (400 * 3 + -1n * 3) = 1050 2n + (1200 + -3n) = 1050 Reorder the terms: 1200 + 2n + -3n = 1050 Combine like terms: 2n + -3n = -1n 1200 + -1n = 1050 Solving 1200 + -1n = 1050 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1200' to each side of the equation. 1200 + -1200 + -1n = 1050 + -1200 Combine like terms: 1200 + -1200 = 0 0 + -1n = 1050 + -1200 -1n = 1050 + -1200 Combine like terms: 1050 + -1200 = -150 -1n = -150 Divide each side by '-1'. n = 150 Simplifying n = 150
| b/13-3b/13=16/13 | | 16+2t=84 | | 6/-.14=.29 | | 6x-9-2(1-x)=x+9 | | 2*0+5y=10 | | (9x+1)+(5x+11)=180 | | 2(x-6)=4(x+2) | | 5n-45=120 | | 4(-8.2)+3.5(100+5)= | | 20=m | | -10x^2y+5xy^2-20xy= | | 5c(7c-5)=0 | | 725.00+10.50x=19.50x. | | (-8)-6= | | 27k-6= | | 3x^2+28x=0 | | y=4(-8.2) | | 12x+4=9x-23 | | 6n=18-2n | | 0.25x+0.4y-1=0 | | 19.50x=2500. | | 8(-1-3p)-5= | | 6+x=-24 | | x/2-x/3=8 | | p-11=-9+p | | 0=1.3v+1 | | 6(4x-5)(4x+3)=0 | | 2-7(x+1)=3(x-2)-5(x+3) | | 756x^18= | | (3x+8)=(5x-2) | | y-1=.5x-7 | | 5x+2=4x+2 |